Ireland : Staff Report for the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This 2005 Article IV Consultation for Ireland reports that economic performance has been impressive, owing in significant measure to sound policies. In line with the global cycle, growth picked up strongly in 2004. Rapid employment growth has been supported by immigration, so the unemployment rate has been roughly unchanged and wage growth remained moderate. Housing price appreciation has slowed, but housing prices are high on various measures. Important progress has been made in preparing for population aging, but there are concerns that households are not saving enough for retirement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet